Application of Blended Learning as an Innovative Social Sciences Learning Innovation Effort After the Covid-19 Pandemic - Syaharuddin Syaharuddin; Ersis Warmansyah Abbas; Yusup Yusup; Hairunisa Hairunisa; Rizky Martha Cahya Puspita; Mutiani Mutiani (The Innovation of Social Studies Journal, 2023)
The development of communication technology in education is very rapid, starting from the development of digital-based learning media to the use of the Learning Management System (LMS), and video conferencing applications that support distance learning. This article aims to describe the application of blended learning so that educators can be interested in applying the blended learning model. The article used literature study research with a mature and in-depth analysis to get results. The blended learning model is a learning model that integrates technology into the learning process. Besides that, this method also combines direct learning, distance learning and independent learning to produce pedagogic aspects that are continuous with one another. Blended learning can be implemented using various learning management system platforms such as Moodle, Schoology, Google Classroom, Edmodo.